The Influence of Literacy, Risk Perception, And Ease on UDINUS Students' Digital Investment Intention - Maxie Suhartanto; Bambang Minarso (Jurnal Ekuilnomi, 2026)
This study examines how Financial Literacy, Risk Perception, and Perceived Ease of Investing influence digital investment intentions of accounting students at Dian Nuswantoro University. A quantitative approach was employed with 115 participants. The results show all variables significantly influence investment intention, with Perceived Ease of Investing emerging as the most dominant factor. The model explains 37.3% of the variance in Investment Intention (Adjusted R Square = 0.373). These findings emphasize the role of cognitive and technological factors in shaping investment behavior and suggest policy implications for financial authorities and universities to strengthen financial literacy education and promote accessible digital investment platforms